Model Regresi Linier Pengaruh Komposisi Kendaraan Terhadap Tingkat Kecelakaan Pada Jalan Tol Surabaya-Gempol - Nur Setiaji Pamungkas; Junaidi Junaidi; Triatmo Sugih Hardono (Politeknik Negeri Semarang, 2013)
Traffic accident is an event in which the unexpected and accidental, involve vehicles with or without other road users, resulting in loss of life or loss of property. The increasing number of vehicles as well as variation of the type and size of four or more wheeled vehicles of various dimensions and specifications of the vehicle, different speeds, driver behavior is not the same that would potentially cause symptoms that lead to the occurrence of traffic accidents on the freeway. This study aimed to determine the effect of the composition of vehicles in traffic flow on the highway accident rate in Surabaya-Gempol. Class composition of vehicles passing through the toll road will be analyzed influence on the rate of accidents (accident frequency = AF). This research is a study area toll roads Surabaya - Gempol that toll roads are divided into 2 lanes and 3 lanes. The method used in this study is the method of multiple linear regression analysis. Results of multiple linear regression analysis showed that only 1 of 4 linear regression model that showed that the variable composition of the vehicle has a significant effect on the frequency rate of accidents. While the other three regression models show the opposite result. This menunujukkan that improper linear regression model to predict the relationship between the independent variable composition with the vehicle accident rate on the highway Surabaya-Gempol.